Menstrual Tracking Apps in India : User Perceptions, Attitudes, and Implications - Nair, Ananthu; K., Padmakumar; Krishna, Sauparnika R. (Indian Journal of Marketing, 2023)
The use of mobile applications as health-tracking platforms has been increasing worldwide. This trend has been observed in India as well. Menstrual tracking applications, or MTAs, are one such category of â€œmHealthâ€ apps that have been gaining popularity. However, the scholarship in this area has not satisfactorily considered this niche phenomenon, especially in the Indian context. This article presented novel findings from a study conducted on 464 women from different parts of the country. A mixed-methods approach was employed to understand user perceptions, knowledge, and practices on MTAs. The study indicated good awareness of MTAs. Women use MTAs for various reasons, from tracking their cycles to planning sexual activity. The women in the study had an overall positive outlook toward MTAs. The insights from the study also suggested the need for various stakeholders, such as the app-makers and regulatory bodies, to step in and recognize some of the concerns of the users. These include issues of data privacy, lack of medical grounding, etc. The article also discussed various implications that are relevant for the stakeholders. The studyâ€™s findings showed that young women in India are embracing their menstruating bodies with the help of digital tools like MTAs. The present study also emphasized the importance of personalization in MTAs to support the varied motives of the users and the need for collaboration between various stakeholders to fulfill user needs.